(untitled) (Texas Journal of Engineering and Technology, 2022)
Wine as an alcoholic drink has been known since ancient time. Various technologies are used for producing high quality wine in different countries. Nowadays several methods of producing wine are spared. Scientists in many countries are working to develop and improve these methods. Scientists are indicating to beneficial characteristics of wine. There is lot of information about beneficial character of grape because of the large amount of biological active materials.